Update on 13 Syndromes Affecting Craniofacial and Dental Structures - Bartzela, Theodosia N.; Carels, Carine; Maltha, Jaap C. (Frontiers in Physiology, 2017)
Care of individuals with syndromes affecting craniofacial and dental structures are mostly treated by an interdisciplinary team from early childhood on. In addition to medical and dental specialists that have a vivid interest in these syndromes and for whom these syndromes are of evident interest, experts of scientific background—like molecular and developmental geneticists, but also computational biologists and bioinformaticians—, become more frequently involved in the refined diagnostic and etiological processes of these patients. Early diagnosis is often crucial for the effective treatment of functional and developmental aspects. However, not all syndromes can be clinically identified early, especially in cases of absence of known family history. Moreover, the treatment of these patients is often complicated because of insufficient medical knowledge, and because of the dental and craniofacial developmental variations. The role of the team is crucial for the prevention, proper function, and craniofacial development which is often combined with orthognathic surgery. Although the existing literature does not provide considerable insight into this topic, this descriptive review aims to provide tools for the interdisciplinary team by giving an update on the genetics and general features, and the oral and craniofacial manifestations for early diagnosis. Clinical phenotyping together with genetic data and pathway information will ultimately pave the way for preventive strategies and therapeutic options in the future. This will improve the prognosis for better functional and aesthetic outcome for these patients and lead to a better quality of life, not only for the patients themselves but also for their families. The aim of this review is to promote interdisciplinary interaction and mutual understanding among all specialists involved in the diagnosis and therapeutic guidance of patients with these syndromal conditions in order to provide optimal personalized care in an integrated approach.